Vortex dynamics in 2H-NbSe2 containing a periodic channel structure - André, M-O. (2000)
Fil: Pastoriza, H. Comisión Nacional de Energía Atómica; Argentina; RijksuniÕersiteit Leiden, Kamerlingh Onnes Laboratorium; Países Bajos